Sovereign Debt Restructurings in Belize: Debt Sustainability and Financial Stability Aspects - Tamon Asonuma; Michael G. Papaioannou; Gerardo Peraza; Kristine Vitola; Takahiro Tsuda (Journal of Banking and Financial Economics)
This paper examines the causes, processes, and outcomes of the two Belize sovereign debt restructurings in 2006–07 and in 2012–13, which occurred outside an IMF-supported program. It finds that the motivation for the two debt restructurings differed, as the former was driven by external liquidity concerns while the latter was motivated by a substantial increase in the coupon rates and future fiscal solvency concerns. Despite differential treatment between residents and non-residents, both 2006–07 and 2012–13 debt exchanges were executed through collaborative engagement, due in part to the existence of a broad-based creditor committee and the authorities’ effective communication strategy. However, while providing temporary liquidity relief, neither of the debt restructurings properly addressed long-term debt sustainability concerns. Going forward, the success of the 2012–13 debt restructuring will still depend on the country’s ability to strengthen fiscal efforts and the public debt management framework.